Hunting Eve [large type] - Johansen, Iris (Johansen, Iris. Eve Duncan forensics thriller., 2013)
In the second book of Iris Johansen's heart-stopping new Eve Duncan trilogy, the stakes get higher. Eve Duncan is on the run. Kidnapped by Jim Doane, a mysterious man who wants her to complete a sinister forensic sculpture, she now has no time to savor the victory of escaping from him. He's back on her trail and closing in fast. Doane desperately needs Eve's skill to reconstruct the skull of his son -- a sick and twisted killer who still holds Doane in thrall from beyond the grave. The CIA has its own reasons for tracking Eve's nemesis. And those closest to Eve -- Joe Quinn and Jane MacGuire -- are doing everything in their power to rescue her, while a hired gun named Lee Zander is on a personal mission to eliminate Doane.